Minimal number of morphoagronomic characters required for the identification of pineapple (Ananas comosus) cultivars in peatlands of Riau, Indonesia - Rosmaina Rosmaina (MBI & UNS Solo, 2021)
Abstract. Rosmaina, Elfianis R, Almaksur A, Zulfahmi. 2021. Minimal number of morphoagronomic characters required for the identification of pineapple (Ananas comosus) cultivars in peatlands of Riau, Indonesia. Biodiversitas 22: 3854-3862. Pineapple (Ananas comosus L Merr)  is a tropical fruit that has high economic value. In Riau Province, Indonesia, pineapples grow and produce well on various types of land, including the highly acidic peatland. There are many types of pineapples grown by  from generation to generation, but so far, there have been no reports regarding the diversity of pineapples in peatlands. This study aimed to determine the minimal number of characters distinguishing pineapple morphological and agronomic characters in peatlands. The observations were done on 24 local genotypes of pineapple in peatlands. Characterization were carried out on 49 morphological and agronomic characters according to the Pineapple descriptor from the International Board for Plant Genetic Resources (IBPGRI). The data were analyzed by Multivariate Analysis, in which the principal components analysis was used for qualitative and quantitative traits. Based on the results of this study, there were at least 12 characters proposed to describe pineapple in peatlands, viz. seven qualitative characters (fruit base leaf color (collar), fruit shape, bractea color, fruit eye profile, fruit eye surface, flesh color, crown attachment to fruit) and five quantitative characters (fruit weight, fruit flesh weight, plant height, number of leaves and leaf length). Out of the 49 traits observed,  12 selected characters can be used as a minimal number of characters that can be used to identify pineapple cultivars on peatland. The findings of this research are rewarding for the conservation and management of genetic resources, selection, and breeding activities of pineapple plants.